Graphene–graphite hybrid epoxy composites with controllable workability for thermal management - Levy, Idan; Wormser, Eyal Merary; Varenik, Maxim; Buzaglo, Matat; Nadiv, Roey; Regev, Oren (Beilstein Journal of Nanotechnology, 2019)
The substantial heat generation in highly dense electronic devices requires the use of materials tailored to facilitate efficient thermal management. The design of such materials may be based on the loading of thermally conductive fillers into the polymer matrix applied – as a thermal interface material – on the interface between two surfaces to reduce contact resistance. On the one hand, these additives enhance the thermal conductivity of the composite, but on the other hand, they increase the viscosity of the composite and hence impair its workability. This in turn could negatively affect the device–matrix interface. To address this problem, we suggest a tunable composite material comprising a combination of two different carbon-based fillers, graphene nanoplatelets (GNPs) and graphite. By adjusting the GNP:graphite concentration ratio and the total concentration of the fillers, we were able to fine tune the thermal conductivity and the workability of the hybrid polymer composite. To facilitate the optimal design of materials for thermal management, we constructed a ‘concentration–thermal conductivity–viscosity phase diagram’. This hybrid approach thus offers solutions for thermal management applications, providing both finely tuned composite thermal properties and workability. We demonstrate the utility of this approach by fabricating a thermal interface material with tunable workability and testing it in a model electronic device.
Keywords: hybrid composites; nanocomposites; rheology; thermal interface material; thermal properties

(untitled) - Garimella, S. V.; Persoons, T.; Weibel, J. A.; Gektin, V. (IEEE Trans. Compon., Packag., Manuf. Technol., 2017)

(untitled) - Samson, E. C.; Machiroutu, S. V.; Chang, J.-Y.; Santos, I.; Hermerding, J.; Dani, A.; Prasher, R.; Song, D. W. (Intel Technol. J., 2005)

(untitled) - Chung, D. D. L. (J. Mater. Eng. Perform., 2001)

(untitled) - Prasher, R. (Proc. IEEE, 2006)

(untitled) - Sarvar, F.; Whalley, D.; Conway, P. P. (Proceedings of the 1st Electronics Systemintegration Technology Conference (Estc 2006), 2006)

(untitled) - Hansson, J.; Zandén, C. (IEEE 16th International Conference on Nanotechnology (IEEE-Nano), 2016)

(untitled) - Kandasamy, R.; Wang, X.-Q.; Mujumdar, A. S. (Appl. Therm. Eng., 2007)

(untitled) - Bhanushali, S.; Ghosh, P. C.; Simon, G. P.; Cheng, W. (Adv. Mater. Interfaces, 2017)

(untitled) - Yu, H.; Li, L.; Kido, T.; Xi, G.; Xu, G.; Guo, F. (J. Appl. Polym. Sci., 2012)

(untitled) - Yu, A.; Ramesh, P.; Itkis, M. E.; Bekyarova, E.; Haddon, R. C. (J. Phys. Chem. C, 2007)

(untitled) - Gojny, F. H.; Wichmann, M. H. G.; Fiedler, B.; Kinloch, I. A.; Bauhofer, W.; Windle, A. H.; Schulte, K. (Polymer, 2006)

(untitled) - Jiménez-Suárez, A.; Moriche, R.; Prolongo, S. G.; Sánchez, M.; Ureña, A. (J. Nano Res., 2016)

(untitled) - Jo, I.; Pettes, M. T.; Kim, J.; Watanabe, K.; Taniguchi, T.; Yao, Z.; Shi, L. (Nano Lett., 2013)

(untitled) - Yu, C.; Zhang, J.; Li, Z.; Tian, W.; Wang, L.; Luo, J.; Li, Q.; Fan, X.; Yao, Y. (Composites, Part A, 2017)

(untitled) - Hu, J.; Huang, Y.; Yao, Y.; Pan, G.; Sun, J.; Zeng, X.; Sun, R.; Xu, J.-B.; Song, B.; Wong, C.-P. (ACS Appl. Mater. Interfaces, 2017)

Handbook of fillers - Wypych, G. (Elsevier, 2006)

(untitled) - Balandin, A. A. (Nat. Mater., 2011)

(untitled) - Huang, Y.; Hu, J.; Yao, Y.; Zeng, X.; Sun, J.; Pan, G.; Sun, R.; Xu, J.-B.; Wong, C.-P. (Adv. Mater. Interfaces, 2017)

(untitled) - Pop, E.; Mann, D.; Wang, Q.; Goodson, K.; Dai, H. (Nano Lett., 2006)

(untitled) - Biercuk, M. J.; Llaguno, M. C.; Radosavljevic, M.; Hyun, J. K.; Johnson, A. T.; Fischer, J. E. (Appl. Phys. Lett., 2002)

(untitled) - Moisala, A.; Li, Q.; Kinloch, I. A.; Windle, A. H. (Compos. Sci. Technol., 2006)

(untitled) - Wang, S.; Qiu, J. (Composites, Part B, 2010)

(untitled) - Kim, H. S.; Jang, J.-u.; Yu, J.; Kim, S. Y. (Composites, Part B, 2015)

(untitled) - Shtein, M.; Nadiv, R.; Buzaglo, M.; Kahil, K.; Regev, O. (Chem. Mater., 2015)

(untitled) - Shtein, M.; Nadiv, R.; Buzaglo, M.; Regev, O. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Bianco, A.; Cheng, H.-M.; Enoki, T.; Gogotsi, Y.; Hurt, R. H.; Koratkar, N.; Kyotani, T.; Monthioux, M.; Park, C. R.; Tascon, J. M. D.; Zhang, J. (Carbon, 2013)

(untitled) - Feng, C.-P.; Bai, L.; Shao, Y.; Bao, R.-Y.; Liu, Z.-Y.; Yang, M.-B.; Chen, J.; Ni, H.-Y.; Yang, W. (Adv. Mater. Interfaces, 2018)

(untitled) - Vinod, S.; Tiwary, C. S.; Samanta, A.; Ozden, S.; Narayanan, T. N.; Vajtai, R.; Agarwal, V.; Singh, A. K.; John, G.; Ajayan, P. M. (Adv. Mater. Interfaces, 2018)

(untitled) - Shahil, K. M.; Balandin, A. A. (2011 11th IEEE Conference on Nanotechnology (IEEE-NANO), 2011)

(untitled) - Cho, E.-C.; Huang, J.-H.; Li, C.-P.; Chang-Jian, C.-W.; Lee, K.-C.; Hsiao, Y.-S.; Huang, J.-H. (Carbon, 2016)

(untitled) - Zakaria, M. R.; Abdul Kudus, M. H.; Md. Akil, H.; Mohd Thirmizir, M. Z. (Composites, Part B, 2017)

(untitled) - Ahmadi-Moghadam, B.; Taheri, F. (J. Mater. Sci., 2014)

(untitled) - Moriche, R.; Prolongo, S. G.; Sánchez, M.; Jiménez-Suárez, A.; Chamizo, F. J.; Ureña, A. (Int. J. Adhes. Adhes., 2016)

(untitled) - Wang, F.; Drzal, L. T.; Qin, Y.; Huang, Z. (J. Mater. Sci., 2015)

(untitled) - Park, J. S.; An, Y. J.; Shin, K.; Han, J. H.; Lee, C. S. (RSC Adv., 2015)

(untitled) - Mu, M.; Wan, C.; McNally, T. (2D Mater., 2017)

(untitled) - Xu, X.; Chen, J.; Zhou, J.; Li, B. (Adv. Mater. (Weinheim, Ger.), 2018)

IEEE International Conference on Dieletrics (ICD) - Wang, W.; Bian, W.; Yang, Y. (2016)

(untitled) - Lee, S. W.; Kwak, G.; Han, Y. S.; Vo, T. S.; Kwon, Y. (Mol. Cryst. Liq. Cryst., 2017)

(untitled) - Prasher, R. S.; Matayabas, J. C. (IEEE Trans. Compon. Packag. Technol., 2004)

(untitled) - Varenik, M.; Nadiv, R.; Levy, I.; Vasilyev, G.; Regev, O. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Gu, H.; Ma, C.; Gu, J.; Guo, J.; Yan, X.; Huang, J.; Zhang, Q.; Guo, Z. (J. Mater. Chem. C, 2016)

(untitled) - Katunin, A.; Krukiewicz, K.; Turczyn, R.; Sul, P.; Łasica, A.; Bilewicz, M. (Compos. Struct., 2017)

(untitled) - Humeau, C.; Davies, P.; Jacquemin, F. (Mater. Des., 2016)

(untitled) - Mohd Radzuan, N. A.; Yusuf Zakaria, M.; Sulong, A. B.; Sahari, J. (Composites, Part B, 2017)

(untitled) - Chen, H.; Ginzburg, V. V.; Yang, J.; Yang, Y.; Liu, W.; Huang, Y.; Du, L.; Chen, B. (Prog. Polym. Sci., 2016)

(untitled) - Krieger, I. M.; Dougherty, T. J. (Trans. Soc. Rheol., 1959)

(untitled) - Dörr, A.; Sadiki, A.; Mehdizadeh, A. (J. Rheol., 2013)

(untitled) - Nadiv, R.; Shachar, G.; Peretz-Damari, S.; Varenik, M.; Levy, I.; Buzaglo, M.; Ruse, E.; Regev, O. (Carbon, 2018)

Polymer rheology: fundamentals and applications - Rudolph, N.; Osswald, T. A. (Carl Hanser Verlag GmbH Co. KG, 2014)

Rheology: principles, measurements, and applications - Macosko, C. W. (Wiley-VCH, 1994)

(untitled) - Knauert, S. T.; Douglas, J. F.; Starr, F. W. (J. Polym. Sci., Part B: Polym. Phys., 2007)

(untitled) - Hill, R. F.; Supancic, P. H. (J. Am. Ceram. Soc., 2002)

(untitled) - Penney, W. (Chem. Eng. J., 1970)

Mixing and Compounding of Polymers - Manas-Zloczower, I. (Carl Hanser Verlag GmbH & Co. KG, 2009)

(untitled) - Teng, C.-C.; Ma, C.-C. M.; Chiou, K.-C.; Lee, T.-M. (Composites, Part B, 2012)

(untitled) - Yu, A.; Ramesh, P.; Sun, X.; Bekyarova, E.; Itkis, M. E.; Haddon, R. C. (Adv. Mater. (Weinheim, Ger.), 2008)

(untitled) - Guan, F.-L.; Gui, C.-X.; Zhang, H.-B.; Jiang, Z.-G.; Jiang, Y.; Yu, Z.-Z. (Composites, Part B, 2016)

(untitled) - Teng, C.-C.; Ma, C.-C. M.; Chiou, K.-C.; Lee, T.-M.; Shih, Y.-F. (Mater. Chem. Phys., 2011)

(untitled) - Safdari, M.; Al-Haik, M. S. (Carbon, 2013)

(untitled) - Chiguma, J.; Johnson, E.; Shah, P.; Gornopolskaya, N.; Jones, W. E., Jr (Open J. Compos. Mater., 2013)

(untitled) - Qi, F.; Tanner, R. I. (Rheol. Acta, 2012)

(untitled) - Farris, R. J. (Trans. Soc. Rheol., 1968)

(untitled) - Ngo, I.-L.; Jeon, S.; Byon, C. (Int. J. Heat Mass Transfer, 2016)

(untitled) - Mehrali, M.; Sadeghinezhad, E.; Latibari, S.; Kazi, S.; Mehrali, M.; Zubir, M. N. B. M.; Metselaar, H. S. (Nanoscale Res. Lett., 2014)

(untitled) - Warzoha, R. J.; Fleischer, A. S. (Int. J. Heat Mass Transfer, 2014)

(untitled) - Al-Ajlan, S. A. (Appl. Therm. Eng., 2006)

(untitled) - Nadiv, R.; Shtein, M.; Shachar, G.; Varenik, M.; Regev, O. (Nanotechnology, 2017)